Applying Composable Architectures to the Design and Development of a Product Line of Complex Systems. Issue 6 (16th February 2017) - Oster, Christopher; Kaiser, Michael; Kruse, Jonathan; Wade, Jon; Cloutier, Rob
ABSTRACT: This paper investigates a composable design methodology leveraging SysML to manage mission flexible product lines, and reviews the application of this methodology to a spacecraft product line. This methodology extends the SysML language with a mathematical and Boolean constraint language allowing for the capture of product line rules as an alternative to a more traditional variation tree. Finally, this paper reviews future work underway to extend this methodology.